Potential Influence of a Developing La Niña on the Sea-Ice Reduction in the Barents–Kara Seas. Issue 3 (27th May 2019) - Luo, Rui; Wu, Zhiwei; Zhang, Peng; Dou, Juan
Abstract: The potential influence of a developing La Niña on Arctic sea-ice annual variability is investigated using both observational data and an atmospheric general circulation model. It is found that during the developing phase of an eastern Pacific (EP) La Niña event in June, July, and August (JJA) and September, October, and November (SON), the sea-ice concentration (SIC) over the Barents–Kara Seas declines more than 15%. The local atmospheric circulation pattern associated with the EP La Niña is characterized as a weak decrease in geopotential height over the Barents–Kara Seas, combined with an anticyclone in the North Atlantic. The corresponding southerly winds push warm waters northward into the key sea-ice reduction region and directly accelerate sea-ice melt. Meanwhile, the abundant moisture contained in the lower troposphere is transported into the Arctic region by winds resulting from the local barotropic structure. The humid atmosphere contributes to both net shortwave and longwave radiation and thus indirectly accelerates the decline in sea ice. Simulations by the European Centre Hamburg Model, version 5.4, are forced by observed sea surface temperature anomalies associated with EP La Niña events. The results of the simulations capture the North Atlantic anticyclone and reproduce the moisture transport, which supports the premise that an EP La Niña plays a crucial role in sea-ice reduction over the Barents–Kara sector from the perspective of atmospheric circulation and net surface heat flux.